Christ the Redeemer - Noll, Elizabeth (Seven wonders of the modern world (Bellwether Media), 2021)
Presents the history, construction, design, and culture of the Christ the Redeemer statue in Rio de Janeiro, Brazil, one of the seven wonders of the modern world. Highlights the engineer behind the statue, and details the updates and upgrades that have been done to the statue over the years. Includes color photographs, fact boxes, a timeline, a glossary, and additional resources.